Hi Larry
x^3 - 168 = [ 24(x-2)] / 2
x^3 - 168 = (24x - 48)/2
x^3 - 168 = 12x - 24
Subtract 12x - 24 to both sides
x^3 - 168 - (12x - 24) = 12xx - 24 - (12x - 24)
x^3 - 12x - 144 = 0
Now, factor the left sides
(x - 6)(x^2 + 6x + 24) = 0
Set factors equal to 0
x - 6 = 0 or x^2 + 6x + 24 = 0
x = 0 + 6 or x^2 + 6x + 24 - 0
x = 6
Answer : X = 6
Good luck !
The anwser is a hope it helps
Answer:
As x goes to negative infinity, g(x) goes to zero.
As x goes to positive infinity, g(x) goes to zero.
(So the answer is the second option)
Step-by-step explanation:
We have the function
First, let's look at what happens when we input smaller and smaller numbers
As we can see, as we input smaller and smaller numbers, the answer gets smaller.
Eventually, these fractions will be so small that they will get closer and closer to zero.
This same thing applies to larger and larger numbers, so the end behavior of each side will both be zero.
Answer:
36
Step-by-step explanation:
u need 12 to make 4 bracelets
4 bracelets x 3 = 12 bracelets
12 beads x 3 = 36 beads
Because there are no parentheses, I'm assuming you're asking for how to factor this using the GCF, which can be done like so:
9−12x+6y
Factor a 3 out of this expression.
3(3 - 4x + 2y)
The expression has been simplified using the distributive property in reverse.